Steam Turbine Performance Variation Based on Operational Parameters: Variasi Kinerja Turbin Uap Berdasarkan Parameter Operasional - A’rasy Fahruddin; Muhammad Iqbal Nur Fadillah; Mulyadi; Rachmat Firdaus (Indonesian Journal of Innovation Studies, 2026)
This study evaluates the performance characteristics of a steam turbine under varying operational conditions in a power generation system. General Background: Steam turbines are essential components in power plants, converting thermal energy into mechanical energy for electricity generation. Specific Background: Turbine performance is influenced by parameters such as steam flow rate, blade configuration, and operating conditions, which determine efficiency and output power. Knowledge Gap: Previous studies have examined turbine performance, yet detailed evaluation under specific parameter variations in practical systems remains limited. Aims: This research aims to analyze turbine performance by examining the relationship between operational parameters and efficiency. Results: The findings show that variations in steam flow and operational parameters result in measurable differences in turbine efficiency, with certain conditions producing higher performance compared to others. Novelty: The study provides a focused analysis of turbine behavior under controlled parameter variations within a practical framework. Implications: The results provide useful insights for optimizing turbine operation in power plants to achieve improved energy conversion and system performance. Keywords: Steam Turbine, Performance, Efficiency, Power Plant, Operational Parameters Key Findings Highlights Parameter variation produces distinct operational characteristics Certain configurations yield higher system performance levels Measured results show consistent trends across testing conditions